2023
DOI: 10.1155/2023/5956154
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Potential of Troxerutin and Chitosan Loaded Troxerutin on Chorioallantoic Membrane Model

Abstract: Angiogenesis is crucial to the development of cancer because it allows the transport of oxygen, nutrients, and growth factors as well as the spread of tumors to distant organs. Inhibitors of angiogenesis prevent the formation of blood vessels that allow tumor cells to shrink, rather than promote tumor growth. Chitosan acts as a carrier for many drugs, since the compound has various properties such as biodegradable, less toxicity, more stable, simple, easy to prepare, and biocompatible. The aim of the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Maintaining a constant and narrow size distribution is crucial for achieving optimal clinical outcomes with nanocarrier formulations [39]. The size and polydispersity index in the present study was comparatively less than the recently published work with chitosan-loaded troxerutin nanoparticles, in which the size and polydispersity index was 692 d•nm and 0.355, respectively [30]. Both particle size and PDI were expected to increase with the addition of lipid components to the formulations [41,42].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Maintaining a constant and narrow size distribution is crucial for achieving optimal clinical outcomes with nanocarrier formulations [39]. The size and polydispersity index in the present study was comparatively less than the recently published work with chitosan-loaded troxerutin nanoparticles, in which the size and polydispersity index was 692 d•nm and 0.355, respectively [30]. Both particle size and PDI were expected to increase with the addition of lipid components to the formulations [41,42].…”
Section: Discussionmentioning
confidence: 55%
“…Recent studies have reported the potential pharmacological benefits of troxerutinloaded nanoparticles by using various polymers like chitosan and selenium [30,31]. In the present study, we aimed to establish the application of TXR loading within nanoparticles by adopting simple methods.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of MMPs in protein degradation can be evidenced by their wide distribution in different groups of vertebrates [44], including mammals [6][7][8][9], birds [45], reptiles [46,47], amphibians [48] and fish [10], as well as insects [49] and echinoderms [50].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, troxerutin protected HacaTcells from UVB-induced decrease in cell growth through regulated miRNA function and suppressed apoptosis ( 25 ). In addition, TRX can reduce Edema and capillary hydrostatic pressure through hyaluronidase and histamine syntheses by TRX application, resulting in the protection of vascular endothelial cells and the effective improvement of microcirculation ( 26 ). Notably, Histamine, 5-hydroxytryptamine, and kinin in venom of jellyfish can operate to contract and spasm vascular smooth muscle and increase the permeability of nearby blood vessels, causing severe discomfort and localized skin congestion and edema ( 7 , 27 ).…”
Section: Introductionmentioning
confidence: 99%